2014
DOI: 10.4314/tjpr.v13i3.24
|View full text |Cite
|
Sign up to set email alerts
|

Photoprotective Effect of Tea and its Extracts against Ultraviolet Radiation-Induced Skin Disorders

Abstract: Ultraviolet (UV) exposure induces photodamage of skin. It is a matter of concern that the level of UV radiation reaching the earth surface is increasing as a result of depletion of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 51 publications
0
10
0
5
Order By: Relevance
“…UV B has indirect detrimental effects on the immune system of the skin, oxidative stress responses, and photoaging [3]. UV A radiation is more than 90 % of atmospheric UV irradiation [2], and it penetrates much deeper into the epidermis and dermis of the skin [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…UV B has indirect detrimental effects on the immune system of the skin, oxidative stress responses, and photoaging [3]. UV A radiation is more than 90 % of atmospheric UV irradiation [2], and it penetrates much deeper into the epidermis and dermis of the skin [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…UV A radiation is absorbed by DNA and reacts with non-DNA chromophores, leading to formation of reactive oxygen species (ROS) which damage DNA, proteins, and lipids in the skin [4,5]. UV A plays a significant role in producing genotoxic bipyrimidine photo-products [6].…”
Section: Introductionmentioning
confidence: 99%
“…Tests using HaCaT cells concluded that green tea polyphenols afforded protection against UV-B induced stress by interacting with UV-B induced reactive oxygen species (ROS) and attenuating mitochondrion-mediated apoptosis [8]. However, these mechanisms need to be evaluated and verified in animal models and/or clinical studies [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…Oral administration of L-cystine and L-theanine during the perioperative period alleviates post-gastrectomy inflammation and promotes recovery after surgery [54]. Supplementation of L-cystine and L-theanine significantly suppresses the exercise-induced fluctuation of blood immunocompetent cells, and helps to reduce alterations of the immune response by both attenuating the rise of neutrophil count and reducing the lymphocyte count caused by extreme endurance exercise [55][56][57].…”
Section: Improving Immunitymentioning
confidence: 99%